Comparision on the Functional Morphology and Morphometry of Lumbosacral Veretebrae in Pug and Native Breed Dogs - Rajathi, S. (Indian Journal of Veterinary Anatomy, 2018)
Comparison on the functional morphology and morphometry of lumbosacral vertebra in pug and native dogs were studied. The six lumbosacral vertebra of both the breeds (three male and three female) were measured and compared for the movement and angulation of the lumbosacral articulation. Each vertebra was morphologically and morphometrically studied and compared among the two breeds. The transverse process was longer in pug when compared to native breed. Centrum was more rounded in pug and elliptical in native dogs. The length of the centrum was more in native dogs which provided more angulation. The pedicle length of pug was higher when compared to native dogs. This proves that the spinal canal was more rounded in pug breed and dorsoventrally compressed in native breed. The distance between the anterior articular process in both the breeds was similar in dimension from L1 to L6 eventhough pug was comparatively small in body size. The height of the supraspinous process was more in native dogs when compared to toy breed. This showed that more musculous and ligamentous attachment in native dogs when compared to toy breeds.